Kedaulatan Rakyat dalam Hak Recall Partai - Mahmud (Jurnal Hukum Berkeadaban, 2025)
This article discusses the issue of people's sovereignty in the context of political parties' right of recall in Indonesia. Recall, which is legally granted to political parties to withdraw legislative members, contradicts the basic principles of democracy that place the people as the highest authority. Through normative juridical research methods using a legislative approach, Constitutional Court decisions, and representation theory, this study finds that the recall right in the hands of parties reflects political oligarchy rather than a mechanism of public accountability. Legislative members tend to be loyal to their parties in order to avoid recall, thereby weakening substantive representation of the people as constituents. A comparison with practices in countries such as the United States and Venezuela shows that recall as a right of the people can strengthen the accountability and legitimacy of public officials. Therefore, legal reform is needed to transfer recall from a political party right to a constituent right, as an effort to restore people's sovereignty, strengthen political representation, and build a more participatory and accountable democratic system.